On the Anion Exchange of PX3(X = Cl, Br, I) in Ionic Liquids comprising Halide Anions - Wolff, Alexander; Pallmann, Julia; Brunner, Eike; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
Mixtures of the phosphorus(III) halides PX3(X = Cl, Br, I) and the ionic liquids [HMIm][X] (X = Cl, Br, I; HMIm = 1-hexyl-3-methylimidazolium) were studied by nuclear magnetic resonance and Raman spectroscopy. The chloride PCl3was found to be stable in all mixtures, whereas PBr3and PI3can undergo halide exchange depending on the anion of the utilized ionic liquid. The exchange occurs immediately after mixing the compounds at room temperature. In contrast to previous observations made in conventional solvents, intermediate mixed phosphorus halides have not been observed in ionic liquids, indicating a rapid exchange under the applied conditions. Compared to the chemical shifts observed in nuclear magnetic resonance spectra of pure PX3liquids, the signal of PCl3is strongly shifted upfield in [HMIm][Cl] indicating strong interaction between the phosphorus halide and the surrounding ionic liquid.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Phosphorus halides; Ionic liquids; Halide exchange; NMR spectroscopy; Raman spectroscopy